2020
DOI: 10.1212/wnl.0000000000010813
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of Parkinson disease

Abstract: Objective:To perform a simultaneous evaluation of potential risk/protective factors of Parkinson’s disease (PD) in order to identify independent risk/protective factors, assess interaction among factors and determine whether identified risk factors predict etiological subtypes of PD.Methods:We designed a large case-control study assessing 31 protective/risk factors of PD, including environmental and lifestyle factors, comorbidities, and drugs. The study enrolled 694 PD patients and 640 healthy controls from si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 27 publications
(34 reference statements)
1
40
0
2
Order By: Relevance
“…Hyposmia may be an early known pre-motor symptom in Parkinson's disease. This raises the possibility of a contribution of COVID-19 in the development of this multifactorial condition [38]. Although few cases of parkinsonism have been described after 2019 novel coronavirus SARS-CoV-2 infection, the causal relationship between COVID-19 and the development of Parkinson's disease is not yet supported by robust clinical/etiopathogenic evidence [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Hyposmia may be an early known pre-motor symptom in Parkinson's disease. This raises the possibility of a contribution of COVID-19 in the development of this multifactorial condition [38]. Although few cases of parkinsonism have been described after 2019 novel coronavirus SARS-CoV-2 infection, the causal relationship between COVID-19 and the development of Parkinson's disease is not yet supported by robust clinical/etiopathogenic evidence [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the subtyping of PD patients is not a mere clinical classification but reflects different pathophysiological mechanisms with different risk factors [ 59 , 60 ], and an integration between different neuroimaging techniques could improve the characterization and treatment of this “salamander” disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of past smoking habits was not different between these groups of PD patients. Epidemiological studies have consistently reported an inverse correlation between tobacco use and PD [ 26 , 27 ]. There is evidence of a functional interaction between dopamine and nicotinic cholinergic systems and that nicotine may contribute to the symptomatic management of nonmotor symptoms in PD, by stimulating the dopamine release in the striatum [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%